The Isolation of Some Types of Fungi from Hard Ticks and the Study of the Effect of Fungi and the Extract Ethanol of the Plant Nerium Olender in the Control it - Habeeb Waseel Kadhum Shubber (Journal of Global Pharma Technology, 2018)
The Fungi Isolated Metathizium anisopliae, Pencilliumsp, Beaveriabassina and Thrichotheciumrosum the last one was isolated for the first time from Hard Ticks. The two types of germinal suspension fungal 'Thrichotheciumvosum and ' exceed in different life stages of Hyalommasppin which the highest proportion of the eggsmortalityis (92.15)% and (89.88) % successively, While in Un fed larvae is (100)% and engorged larvae is (92.4)% and it reached in un fed larvae (100)% and (80.4)% for the engorged larvae successively and it reached in un fed nymphs (86.2)% and in engorged nymphsit was (54.4)% and un fed nymphs (66)% while in engorged nymphsIt reached (20)% successively while the highest level is 108 while the lowest activity is the fungus Pencillium sp. While in the advanced stages was noticed as a perfect in planet extracts it reached the highest proportion of mortalityis (81.3)% in related to un fed adult and (72.4)% in related to engorged adult and the fungal filtrate exceeded the fungal extracts in causing mortality proportion.Keywords: Hard Ticks, Fungi, Plant extracts.